STRATEGI GURU TAHFIDZ DALAM MENINGKATKAN KUALITAS HAFALAN ALQURAN SISWA-SISWI DI SDTQ AL FAJRI SAWANGAN, DEPOK - Susiatun (PT. Hasba Edukasi Mandiri, 2025)
The learning of Qur’anic memorization (tahfidz Al-Qur’an) is an important component in shaping the religious character of students in Islamic schools, including at SDIT-TQ Al Fajri Sawangan, Depok City. The quality of students’ memorization is not only determined by individual ability, but is also strongly influenced by the strategies used by tahfidz teachers in guiding the processes of memorizing and muraja’ah (revision). This condition forms the background of the present study, which aims to examine the strategies employed by tahfidz teachers to improve students’ Qur’an memorization quality, as well as to identify the supporting and inhibiting factors that arise during its implementation. This research uses a qualitative approach with a case study method. Data were collected through observations of tahfidz activities, in-depth interviews with tahfidz teachers, the school principal, and several students, as well as documentation of the school’s tahfidz learning program. Data analysis was carried out through data reduction, data presentation, and conclusion drawing in order to obtain a comprehensive picture of the implementation of tahfidz learning strategies. The results of the study show that tahfidz teachers apply various strategies, such as talaqqi and musyafahah, tikrar (repetition), daily memorization submissions, scheduled muraja’ah, as well as providing motivation and rewards. Supporting factors include teacher competence, the school’s religious environment, parental support, and a well-structured tahfidz program management. Meanwhile, the obstacles identified include differences in students’ abilities, uneven levels of motivation, and limited study time.